High methoxyl pectin/apple particles composite gels: Effect of particle size and particle concentration on mechanical properties and gel structure - Genovese, Diego Bautista (2010)
In order to study the effect of fruit pulp on the structure of fruit jams, they were modeled as composites with a high-methoxyl pectin (HMP) gel matrix filled with apple particles. The effect of particle concentration (0, 1 and 2 wt%) and particle size (small: < 125 μm, and large: 125-850 μm) on a pectin gel (0.5 wt% HMP, 65 wt% glucose, pH 3.0, 0.1 M citrate buffer) were studied. Rheological measurements showed that increasing concentration of small particles produced a significant increase in the elastic modulus of the composite gels. Penetration tests showed that 1 wt% small particles produced a significant decrease of gel strength, rupture strength, adhesiveness and brittleness. Increasing particle size produced a further decrease of these properties (only significant for gel strength). When concentration of small particles was raised to 2 wt%, these parameters (except brittleness) increased back to the control sample (0% particles) values. PRACTICAL APPLICATIONS: Knowledge of the effect of fruit particles on the structure of pectin gels would allow controlling the rheological and mechanical properties of fruit jams in terms of the size and concentration of fruit pulp used in their formulation. © 2010 Wiley Periodicals, Inc.